Analisis Penerapan Laporan Keuangan Organisasi Nirlaba Berdasarkan Psak No. 45 Pada Yayasan Pembangunan Dan Pendidikan Jihadul Ilmi Medan - Tanti Rahayu; Alistraja Dison Silalahi; Debbi Chyntia Ovami (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the suitability of PSAK No. 45 concerning the Financial Reporting of Non-Profit Organizations and the financial reports of the Jihadul Ilmi Education and Development Foundation. The background of this research is the existence of PSAK No. 45 issued by the Indonesian Institute of Accountants (IAI) as a reference in preparing financial reports for non-profit organizations. Conducted at the Jihadul Ilmi Education and Development Foundation where this foundation is a waqf foundation that manages an Islamic college. This research is descriptive qualitative where the data collection technique is by conducting observations, interviews and documentation. The data analysis technique in this research is qualitative analysis. The results of the analysis show that the financial statements of the Jihadul Ilmi Development and Education Foundation have not fully implemented PSAK 45 because the components of the financial statements as outlined in PSAK 45 should consist of activity reports, reports on changes in financial position, cash flow statements and notes on financial statements but the foundation only has 3 components, namely activity reports, statements of changes in financial position and cash flow statements. Notes on financial statements are not made..